Dissecting dentine–pulp injury and wound healing responses: consequences for regenerative endodontics. (6th February 2019) - Duncan, H. F.; Cooper, P. R.; Smith, A. J.
Summary: A thorough understanding of the biology of the dentine–pulp complex is essential to underpin new treatment approaches and maximize clinical impact for regenerative endodontics and minimally invasive vital pulp treatment (VPT) strategies. Following traumatic and carious injury to dentine–pulp, a complex interplay between infection, inflammation and the host defence responses will occur, which is critical to tissue outcomes. Diagnostic procedures aim to inform treatment planning; however, these remain clinically subjective and have considerable limitations. As a consequence, significant effort has focussed on identification of diagnostic biomarkers, although these are also problematic due to difficulties in identifying appropriate diagnostic fluid sources and selecting reproducible biomarkers. This is further compounded by the link between inflammation and repair as many of the molecules involved exhibit significant multifunctionality. The tertiary dentine formed in response to dental injury has been purposefully termed reactionary and reparative dentine to enable focus on associated biological processes. Whilst reactionary dentine produced in response to milder injury is generated from surviving primary odontoblasts, reparative dentine, in response to more intense injury, requires the differentiation of new odontoblast‐like cells derived from progenitor/stem cells recruited to the injury site. These two diverse processes result in very different outcomes in terms of the tertiary dentine produced and reflect the intensity rather than specific nature (nonexposure versus exposure) of the injury. The subsequent identification of the odontoblast‐like cell phenotype remains challenging due to lack of unique molecular or morphological markers. Furthermore, the cells ultimately lining the newly deposited dentine provide only a snapshot of events. The specific source and plasticity of the progenitor cells giving rise to the odontoblast‐like cell phenotype are also of significant debate. It is likely that improved characterization of tertiary dentine may better clarify the influence of cell derivation for odontoblast‐like cells and their diversity. The field of regenerative endodontics offers exciting new treatment opportunities, and to maximize outcomes, we propose that the term regenerative endodontics should embrace the repair, replacement and regeneration of dentine–pulp.